Whole genome analysis for plant growth promotion profiling of Pantoea agglomerans CPHN2, a non-rhizobial nodule endophyte - Kumar, Pradeep; Rani, Simran; Dahiya, Priyanka; Kumar, Ajit; Dang, Amita Suneja; Suneja, Pooja (Frontiers in Microbiology, 2022)
Reduction in agricultural produce and issues like nutrient depleted soil, eutrophication, and ground water contamination have driven the attention towards use of endophyte based bioformulations to restore soil fertility. Pantoea agglomerans CPHN2, a non-rhizobial nodule endophyte, isolated from Cicer arietinum, possessed multiple plant growth promoting traits. In this study, we have analyzed the information on whole genome sequence of this plant growth promoting endophytic bacteria using NextSeq500 technology. The genome of P. agglomerans CPHN2 has a length of 4,839,532 bp and a G + C content of 55.2 percent. The whole genome comprised of three different genomic fractions that include one circular chromosome and two circular plasmids. The comparative analysis was performed between P. agglomerans CPHN2 and 10 genetically similar strains using bacterial pan genome pipeline. All the predicted and annotated gene sequences for plant growth-promotion (PGP), such as phosphate solubilization, siderophore synthesis, nitrogen metabolism, and Indole-3-acetic acid (IAA) of Pantoea agglomerans CPHN2 were identified. The whole genome analysis of Pantoea agglomerans CPHN2 provides an insight into the mechanisms involved in plant growth promotion by endophytes and their potential applications as biofertilizer.